2018
DOI: 10.1002/ccd.27622
|View full text |Cite
|
Sign up to set email alerts
|

Sex disparities in acute myocardial infarction care and outcomes

Abstract: Women with AMI who underwent PCI with XIENCE DES have higher all-cause mortality at one year in compared to men. Region based outcomes demonstrated increased MACE among US patients compared to the patients from China and Japan. After adjusting for differences in demographics, major bleeding, rather than female sex, predicted the higher observed all-cause mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…We also found an increased rate of MACE events in women. These results are similar to those of other recent studies, which show higher incidence of MACE in women than in men, mainly due to poorer cardiovascular risk factor profile and older age [ 30 ], but also due to increased bleeding risk [ 31 ]. Overall, mortality rates were higher in our study compared to those reported in Western Europe.…”
Section: Discussionsupporting
confidence: 92%
“…We also found an increased rate of MACE events in women. These results are similar to those of other recent studies, which show higher incidence of MACE in women than in men, mainly due to poorer cardiovascular risk factor profile and older age [ 30 ], but also due to increased bleeding risk [ 31 ]. Overall, mortality rates were higher in our study compared to those reported in Western Europe.…”
Section: Discussionsupporting
confidence: 92%
“…Cardiovascular disease is the leading cause of death in women . Following percutaneous coronary intervention (PCI), women suffer disproportionately high rates of death, bleeding and complications including myocardial infarction (MI) and stroke . Furthermore, female gender is an independent predictor of death, MI, stent thrombosis and target lesion revascularization after PCI of calcific coronary lesions …”
Section: Introductionmentioning
confidence: 99%
“…There are sex differences in the incidence, pathophysiology, and clinical presentation of heart disease. Women with ischemic heart disease have worse outcomes and are less likely to receive timely treatment than men [ 47 , 48 ]. More women, after menopause, have dyslipidemia than men [ 47 ], which is seen from the results of this study.…”
Section: Discussionmentioning
confidence: 99%